Wet in situ transesterification of microalgae using ethyl acetate as a co-solvent and reactant. (April 2017) - Park, Jeongseok; Kim, Bora; Chang, Yong Keun; Lee, Jae W.
Highlights: EtOAC is firstly used as a single reactant and co-solvent for in situ transesterification. EtOAC hydrolysis yields the EtOH/EtOAC system without using a co-solvent. EtOAC provides higher FAEE yield and saccharification than EtOH/chloroform. 97.8% FAEE yield occurs at 113.6 °C with 4.06 M H2 SO4 and 6.67 ml EtOAC/g dried algae. Abstract: This study addresses wet in situ transesterification of microalgae for the production of biodiesel by introducing ethyl acetate as both reactant and co-solvent. Ethyl acetate and acid catalyst are mixed with wet microalgae in one pot and the mixture is heated for simultaneous lipid extraction and transesterification. As a single reactant and co-solvent, ethyl acetate can provide higher FAEE yield and more saccharification of carbohydrates than the case of binary ethanol and chloroform as a reactant and a co-solvent. The optimal yield was 97.8 wt% at 114 °C and 4.06 M catalyst with 6.67 ml EtOAC/g dried algae based on experimental results and response surface methodology (RSM). This wet in situ transesterification of microalgae using ethyl acetate doesn't require an additional co-solvent and it also promises more economic benefit as combining extraction and transesterification in a single process.